Model Pendekatan Holistik dalam Pemberdayaan Ekonomi Keluarga Melalui Pelatihan Pengembangan Bisnis dan Edukasi Keuangan - Andy Sylvana; Nindya Farah Dwi Puspitasari; Dina Noval Madurani; Maya Maria (Civiliza Publishing, 2025)
The FEB-UT National Community Service Program (PkM) is here to answer the real challenges faced by PKK women in Pondok Cabe Udik Village. Based on the needs analysis, three root problems were revealed: limited practical skills, lack of innovation in creating business opportunities, and weak foundations of family financial management. As a solution, the PkM team carries a comprehensive strategy for women's economic empowerment. The program does not only stop at awareness, but also steps into hands-on training and ongoing mentoring to turn potential into a real home-based venture. The program is carried out with a focus on three main activities, namely training on processing used cooking oil waste into value-added products such as candles and soap, home business development training through shoe washing services, and education and consulting on family financial management. The training is carried out in stages through presentations, demonstrations, workshops, and interactive discussions. The results of the activity showed a significant increase in the aspects of knowledge, skills, and motivation of participants to develop a household-based small business. Participants also began to understand the importance of environmentally friendly household waste management and apply green economy principles in daily activities. In addition, this activity strengthens the participants' ability to manage family finances independently and efficiently. Overall, PkM activities have a positive impact on improving economic welfare, environmental awareness, and social independence of participants, and are expected to become a model of sustainable community empowerment at the local level.